Morphology growth curve of female cross breed duck between Pekin and White Mojosari - A Suparyanto; H Martojo; P.S Hardjosworo; L.H Prasetyo (Jurnal Ilmu Ternak dan Veteriner, 2004)
Morphological growth is a very dynamic process. It is reflected the changes of body structure affected by genetic and environmental responses. Each parameter had different growth curve sigmoid pattern those expressed different characteristics. Phenotypic growth data were collected from female ducks resulted from crossbreed between Pekin male and White Mojosari. The hatchers were twicely collected, the first collection was 69 heads and then they were 89 heads. Equation of non-linier regression is determined by Gompertz model using the Marquardt method. Result showed that fast growth happened from the start to 30 days old. Estimation values of circumstance and depth brest length variables were 30 and 83 mm respectively. In the first derivation, the maximum size of back and brest were observed on 16 weeks old. In the second derivation the maximum sizes of wide hip, wide and depth brestes were reached for longer time, those were 22 to 25 weeks. Meanwhile, the correlation between parameter A (body mature) and k (rate of mature) was negative. Every variable had different oscillation slopes, the slope of two infexion points of the original curve or they were variative.     Key words: Duck, growth curve, morphology, crossbreed